Oral healthcare and technologies breakthroughs in research and practice (Critical explorations., 2017)
"This book is a comprehensive resource with the latest scholarly perspectives on the technological advancements and real-world applications for oral hygiene and medical care. Featuring extensive coverage across a range of relevant perspectives and topics, such as disease management, healthcare administration, and medical informatics"--Provided by publisher.